Preparación deportiva de los integrantes de la selección de Karate Do de la Universidad de Quindío a partir de un programa sistemático de entrenamiento de la fuerza explosiva.Preparación deportiva de los integrantes de la selección de Karate Do de la Universidad de Quindío a partir de un programa sistemático de entrenamiento de la fuerza explosiva (2014)
This research aims to contribute to the sports training of the members of the selection of Karate uniquindio, from a systematic program of training explosive strength, starting with a fitness phase, followed by a phase of anatomical adaptation, work with weights using recyclable materials, floor work and Fitball and finally a specific job with rubbers bike, working movements, kicks and punches to help explosive force. Working with a population of 8 athletes who have a variety of ages and pursuing various university programs. To whom they apply and test a series of planned and structured training which will help contribute to the explosive force and other skills and get a good physical, mental, technical, tactical performance skills.